Implementing the policy of inclusion in Iceland: Teachers’ views and proposals for action - Óskarsdóttir, Edda; Gunnþórsdóttir, Hermína; Svanbjörnsdóttir, Birna María; Sigþórsson, Rúnar (Menntavísindasvið Háskóla Íslands, 2021)
Inclusive education is a prominent feature of Icelandic educational policy. However, an external audit by the European Agency for Special Needs and Inclusive Education (2017) revealed that even though the policy is clear, administrators and practitioners within the school system lack clarity about the concept of inclusion and a deeper understanding of what constitutes inclusive practices in schools.One of seven main recommendations of the audit is to “Ensure that all stakeholders understand inclusive education as the basis for high-quality education for all learners”, and, to that end, organise “national and local-level dialogue about the kind of schools and learning communities that stakeholders want and the best ways to achieve/develop those” (p. 16). To respond to this recommendation, 23 meetings were held across Iceland to discuss the advancement of education for all, organised by a task force assigned by the Ministry of Education and Culture. Representatives of preschools, primary and secondary schools, leisure services, parents, municipal school services, social services and health care from all Icelandic municipalities were invited to the meetings. At the meetings, participants worked on projects in groups of six to eight. Each group was asked to agree on the ten most important actions to promote education for all and to prioritize them as a pyramid so that the most important action would come first, then two in second place, three in third, and so on. Each group’s pyramid was then analysed in order to form a single pyramid reflecting the common conclusion of the groups.The aim of this paper is twofold: The first aim is to present the findings from the 23 meetings based on the analysis described above. The conclusions contain three themes: 1) External framework, cooperation and education; 2) attitudes, support, policy and vision; 3) students, learning, and teaching. The first theme focused on reviewing the guidelines of the Municipalities Equalization Fund so that the allocation of funds would be ...